Marthanda Varma Sankaran Valiathan - Indira Nath (CURRENT SCIENCE, 2014)
M. S. Valiathan, as he is popularly known, can be best described as an intel- lectual wanderer par excellence. Folk history would remember him as the first physician scientist of modern India who married medicine to technology, thereby bringing relief to many and enhancing national pride in medical devices and biomaterials. He was a wanderer geogra- phically in his early professional life like so many doctors of that era. In later years, his nomadic nature took him to cross many disciplines and address many intellectual challenges. But always he remained a wanderer even when physi- cally rooted to south India